Functional Impairment in Borderline Personality Disorder: The Mediating Role of Perceived Social Support - Thadani, Beatriz; Pérez-García, Ana M.; Bermúdez, José (Frontiers in Psychology, 2022)
Borderline personality disorder (BPD) is characterized by instability in relationships, mood fluctuations, and erratic behavior. This study investigates the relationship between pathological personality traits and functional disability, the status of perceived social support in BPD, as well as its mediating role in this relationship. In this cross-sectional study, 192 Spanish women (BPD group, N=97; healthy control group, N=95) completed, through two online platforms, a battery of tests including: the Personality Inventory for DSM-5 Brief Form (PID-5-BF), the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) and the Perceived Social Support subscale of the Quality of Life Questionnaire (QLQ). The results show that perceived social support was significantly lower in the BPD group, which also presented a significantly higher disability score than the control group. Pathological personality traits affected functionality both directly and indirectly through perceived social support, as this variable was a significant mediator in both groups. We conclude that perceived social support is impaired in BPD patients, and enhancing it as a complementary therapy to evidence-based treatments could help preserve the functionality of patients while pathological traits are regulated. This study also encourages future research to delve into the relevance of other psychosocial variables on the functionality of subjects with BPD, and the need of enhancing them in therapy.